Supplementation of evening primrose oil (EPO) - benefits and limitations. Results of the latest studies - Sylwia Grosman; Aleksandra Winiarz; Katarzyna Wąsala; Wojciech Wokurka; Michał Turek; Paula Szlendak; Katarzyna Toś; Kacper Wojtala; Agata Węgrzyniak; Dominik Drobek (Kazimierz Wielki University, 2023)
Introduction One of the most frequently used herbal drugs in the pharmaceutical industry is Oenothera biennis, traditionally called evening primrose. Oil extracted from seeds of a plant is a rich source of unsaturated fatty acids- omega 6 essential fatty acids (EFAs). Healing properties of evening primrose oil (EPO) have been used for ages in order to alleviate symptoms of various medical conditions. Nowadays, studies and clinical trials are conducted with the aim of verifying its effectiveness. The aim of the study Summarize current knowledge on the effectiveness of evening primrose oil in treatments of various diseases. Material and methods The search of the Pubmed database was carried out using keywords, in order to find the latest publications.  Summary  Despite limitations, research shows that supplements containing evening primrose oil (EPO) demonstrate promising results in treatments of various medical conditions, including menopause, premenstrual syndrome, skin problems or multiple sclerosis. However,  more well-designed clinical trials are needed to evaluate long-term effectiveness.